Esterification for biofuel synthesis over an eco-friendly and efficient kaolinite-supported SO42−/ZnAl2O4 macroporous solid acid catalyst. (15th December 2018) - Wang, Anqi; Wang, Junxia; Lu, Can; Xu, Mingliang; Lv, Jianhang; Wu, Xiuling
Graphical abstract: An eco-friendly raw kaolinite was used as a novel support to synthesize a highly efficient S/ZA-Kao macroporous solid acid catalyst for typical esterification reactions of oleic acid with methanol and acetic acid with n -butanol in the synthesis of green biofuels. Highlights: A raw kaolinite-supported SO4 2− /ZnAl2 O4 macroporous solid acid was synthesized. The dispersion, textural and properties of catalysts can be adjusted to optimum. Biodiesel produced via oleic acid esterification with the conversion of 70.1%. Bio-oils upgraded via acetic acid esterification with the conversion of 98.2%. Improved reusability was showed in acetic acid and oleic acid esterification. Abstract: A series of raw kaolinite-supported SO4 2− /ZnAl2 O4 (S/ZA-Kao) macroporous solid acid catalysts were synthesized and applied in esterification of both oleic acid with methanol and acetic acid with n -butanol for the biofuels synthesis. The structures and acidic properties of S/ZA-Kao catalysts were characterized by means of XRD, FE-SEM, EDS, BET, FT-IR (direct and NH3 adsorbed), NH3 -TPD, TG and XPS. The results indicated the mass ratio of ZnAl2 O4 /kaolinite played a significant role in adjusting the active components dispersion, textural and acidic properties. The optimal S/ZA-Kao(6:4) catalysts performed the macroporous structure and the high dispersion of active components, which might be the essential reason for its improved acid sites and reduced limitation of mass transfer. As a result, the macroporous solid acid exhibited superior conversion of 98.2% in acetic acid esterification and 70.1% in oleic acid esterification. The kinetic study demonstrated that the relatively lower values of activation energy over the S/ZA-Kao(6:4) macroporous solid acid, further confirming that the macroporous solid acid was highly efficient for the biofuel synthesis via esterification. Moreover, the further investigation indicated the catalytic activities were closely related to the ratio of Brönsted acid sites on catalysts. Besides, S/ZA-Kao(6:4) macroporous solid acid particularly displayed excellent reusability, which was due to its structural stability and high dispersion of active components.